Pascal's wager - Grumball, Kevin Shaun (2013)
Pascal's Wager, discussed in his Pensées, has provoked discussion and strong views ever since its publication. In it, he proposes: Either God is or he is not. But to which view shall we be inclined? Reason cannot decide this question.ⁱ In this thesis I hope to make a contribution to the ongoing debate by setting Pascal's Wager into a modern decision-making context, providing a taxonomy of objections to the Wager and developing a critical framework which can be used to systematically examine each category in turn to see whether an objection holds. I will also present a new approach to handling 'mixed' strategies, as suggested by Alan Hájek and others, which uses a heuristic model of our perception of infinite rewards. I hold that Pascal's remedy for the unbeliever is a therapeutic response which is entirely in line with modern psychological practice and should not offend moral sensitivities, because it is purely an experiment to see whether faith can naturally arise once the objections are temporarily set aside. I argue that Pascal's Wager needs to be seen as an exercise in personal risk management and that Pascal anticipated both modern decision theory and the associated psychology of how we make choices in formulating his Wager. I suggest that if we understand it in this light, employing the critical toolkit that I assemble, then Pascal's Wager holds against all current objections. ⁱ Blaise Pascal, Pensées, trans. A. J. Krailsheimer (London: Penguin, 1995). 122. L418